2020
DOI: 10.48550/arxiv.2007.05782
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chern-Dold character in complex cobordisms and theta divisors

V. M. Buchstaber,
A. P. Veselov

Abstract: We show that the theta divisors of general principally polarised abelian varieties can be chosen as smooth irreducible algebraic representatives of the coefficients of the Chern-Dold character in complex cobordisms and describe the action on them of the Landweber-Novikov operations. The link with Milnor-Hirzebruch problem about algebraic representatives in the complex cobordisms is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In addition, G 6,2 is of particular importance in algebraic geometry being one of the six Severi varieties, [21]. For n = 6 we start with the manifold together with the point S = (1 : 1) 6 . At this point any of these two subvarieties intersect.…”
Section: The Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, G 6,2 is of particular importance in algebraic geometry being one of the six Severi varieties, [21]. For n = 6 we start with the manifold together with the point S = (1 : 1) 6 . At this point any of these two subvarieties intersect.…”
Section: The Main Resultsmentioning
confidence: 99%
“…It is well known fact that M(0, 5) is the del Pezzo surface of degree 5, while algebro-geometric characterization of the space M(0, n) for n > 5 is an open well known problem. In the paper [6] it has been shown that the problem of algebro-topological characterization of these spaces is related to well known problems of complex cobordisms theory.…”
Section: Introductionmentioning
confidence: 99%
“…The cohomology rings of the spaces M(0, n) were described in [22] (see also [21]). Complex cobordism classes of the spaces M(0, n) are important for applications of the Chern character to complex cobordism theory; see [6] and [4].…”
mentioning
confidence: 99%
“…We are as yet unsure of the relationship between the quantum deformation of cobordism-theory obtained by incorporating our invariants into the product and the deformation recently introduced by Buchstaber-Veselov in[1].…”
mentioning
confidence: 99%